Distal foot reconstruction using distally based fi rst web fl ap: A case series - Ram Mohan; Naveen Kumar; Manoj K Jha; Umesh N; Anchit Kumar (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Background: The reconstruction of distal foot for various defects or contractures mainly over or near the toes has always been a diffi cult task. A fl ap distally based on fi rst web space is dependent upon a perforator arising from the the distal communicating artery between the fi rst dorsal and plantar metatarsal arteries, can be used for the coverage of the toe or the distal foot defects. Method: An observational study was conducted with the study period from August 2016 till August 2018. 10 patients with toe defects and contractures at the dorsum of the distal foot were operated using distally based fl ap elevated from fi rst webspace. Patient's demographic data were collected and evaluated in terms of various factors.